Evaluasi Materi Bahasa Inggris Mahasiswa Program Studi Manajemen Tata Boga di Politeknik pariwisata - Hardina, Hardina (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
English has a role that varies according to its function. In the hotel and restaurant sector, the staff in charge of serving customers both local and foreign customers. For this reason, English language skills also need to be prioritized. However, it is found that many English teachers are not related to the needs of students, one of which is in the Culinary Arts department at the Bali Tourism Polytechnic. This study uses a descriptive method with the concept of English for Specific Purposes (ESP) which is divided into subjective data analysis and objective data analysis. Subjective analysis data were collected through questionnaires distributed to 15 tourism workers or graduate users in restaurants and hotels, while objective analysis data was carried out through analysis of material documents that had been given to students. From this analysis, it can be seen that the types of English skills that must be mastered by students of the Culinary Arts department at the Bali Tourism Polytechnic include listening, speaking, writing, and reading where speaking and listening skills are needed.